2021
DOI: 10.1016/j.jad.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and its correlates among children and adolescents during COVID-19 school closure: The importance of parent-child discussion

Abstract: Highlights A representative sample of 4,342 primary and secondary school students were investigated. The three most prevalent symptoms were: anxiety (24.9%), depression (19.7%), and stress (15.2%). Students were generally satisfied with life and 21.4% became more satisfied with life. Perceived benefit and parent-child discussion were protective factors of mental health. Parent-child discussion was related to less sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
474
3
70

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(580 citation statements)
references
References 24 publications
33
474
3
70
Order By: Relevance
“…Other studies had also found the increased mental health burden among the children and adolescents. One study in China, during the COVID-19 pandemic, showed most prevalent symptoms among children and adolescents were anxiety 24.9 %, depression 19.7 % and stress 15.2 % ( Tang et al, 2020 ). Another study in China showed 19 % adolescents suffer anxiety ( Qi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies had also found the increased mental health burden among the children and adolescents. One study in China, during the COVID-19 pandemic, showed most prevalent symptoms among children and adolescents were anxiety 24.9 %, depression 19.7 % and stress 15.2 % ( Tang et al, 2020 ). Another study in China showed 19 % adolescents suffer anxiety ( Qi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported serious changes in the mental health of children and adolescents during the COVID-19 quarantine [ 5 ]. For example, research carried out in China informed an increase in depressive, anxiety and stress symptoms during the COVID-19 lockdown [ 6 , 7 ]. A recent narrative review analyzed the impact of COVID-19 and lockdown on the mental health of children and adolescents and suggested that young children show more clinginess, poor appetite, inattentiveness, and significant separation problems [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…pour déterminer leurs réponses émotionnelles et comportementales. Il a ainsi été démontré que lorsque les « figures référentes » arrivent à sécuriser l’enfant et à lui expliquer la situation, ce dernier présente un meilleur niveau de bien-être psychologique [11] , [12] . À l’inverse, avoir un parent anxieux ou déprimé lors d’une épidémie augmente le stress ressenti par l’enfant [13] .…”
Section: Les Conséquences Psychiatriques En Population Pédiatrique Enunclassified